Open innovation practices adopted by private stakeholders: perspectives for living labs. Issue 4 (8th June 2015) - Pieter Ballon, Mr Dimitri Schuurman, Dr; Lapointe, Dominic; Guimont, David
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to explore the role of private stakeholders in the living lab (LL) ecosystem and the relationship of private stakeholders to open innovation (OI) practices. There is extensive literature on private stakeholders and OI, but seldom mention is made on the specific question of how private stakeholders integrate OI in the context of a LL. Design/methodology/approach – The authors will analyze qualitatively how private businesses that have participated in a in situ open innovation evaluate and perceived their open innovation practices. Therefore, how they relate to open innovation. Then, the authors will identify a typology of the businesses in relation to OI. Findings – The research focused on the relationship of private stakeholders to OI in the context of in situ OI activities. The results obtained are consistent with literature on OI (Chesbrough, 2003). However, there are differences: if the elements mentioned by the respondents are described in literature, their representation of OI and its components allows us to affirm that this practice is not generalised and that it is often open to interpretation. That emphasises the importance of the role LLs can play as intermediaries to accompany private stakeholders in the OI process. Private stakeholders look for a guide to develop their OI know-how and find their way in the OI ecosystem. Originality/value – The value of this paper is to bridge the research on OI done with private organisation and the research on LLs. The research literature did not pay much attention to the representation of the private stakeholders in the OI ecosystem. This paper has provided the start to open up that field.